Studi Desain Reklamasi Dengan Timbunan Bertahap dan Prefabricated Vertical Drain dengan Metode Elemen Hingga - ONGGO, Anthonius; TARIGAN, Simon Dertha (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2019)
Soft clay substantial settlement and requires longer time to finish consolidation. The observed project in this study is reclamation project. Reclamation is carried out with a gradual piling method so that the strength gain occurs in the soil layer under reclaimed soil. Piling is done repeatedly, with an initial elevation of +2m, second piling with a total elevation of +5m, and the third piling with a total elevation +8mASL. Piling material in this project is compacted sand material, with specified specifications. The use of sand material results in the potential for liquefaction. Therefore it is necessary to conduct soil improvement, and PVD with preloading is chosen which is useful for accelerating the consolidation time. The Prefabricated Vertical Drain method is installed along the reclamation area. This study aims to analyze the soil settlement over time both using PVD and without using PVD. The effect of PVD installation by preloading was analyzed using PLAXIS 2D with axisymmetric for single-drain, and was further modeled in multi drain using plane strain. Single drain modeling into multi drain needs to be done axisymmetic equivalence to plane strain. The soil parameters used are the results of the N-SPT value correlation from various sources.